Endoscopic submucosal dissection of coexisting early esophageal carcinoma and leiomyoma: a case report and review of the literature. Issue 10 (October 2020) - Liang, Ma; Fei, Ding; Jianguo, Song; Changping, Wu; Juan, Dai; Yin, Zhang; Liwen, Zhang; Jianping, Chen
The occurrence of early esophageal cancer located within an area of leiomyoma is extremely rare, and its clinical features and treatment methods have not been well described. We herein report the clinical characteristics, diagnosis, and treatment methods of early esophageal cancer that developed on top of a leiomyoma in the upper third of the esophagus in a 78-year-old woman. All tumor marker concentrations were normal. The leiomyoma was correctly diagnosed as a submucosal tumor by endoscopy and endoscopic ultrasonography. Endoscopic biopsy revealed esophageal squamous cell carcinoma. Both lesions were successfully treated by endoscopic submucosal dissection. The patient was followed up for 6 months without recurrence. Endoscopic submucosal dissection was a successful initial treatment method for esophageal carcinoma coexisting with esophageal leiomyoma in this case.